2020
DOI: 10.1080/13588265.2020.1807687
|View full text |Cite
|
Sign up to set email alerts
|

Modelling head injury due to unmanned aircraft systems collision: Crash dummy vs human body

Abstract: Recent developments in the concept of UAS operations in urban areas have led to risk concerns of UAS collision with human. To better understand this risk, head and neck injuries due to UAS collisions have been investigated by different research teams using crash dummies. Because of the limitations in biofidelity of a crash dummy, head injury level for a crash dummy impact may differ from the human body impact. Therefore, the aim of this paper is to investigate differences in head and neck injuries subject to U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…This human body model can be seen in Figure 7. The comparison of these novel integrated MBS model simulations has shown that there is a discrepancy between the Hybrid III ATD and a human body model for head and neck injury [16,17]. Neck loads were found to be different fundamentally between the crash dummy and the human model.…”
Section: Mbs Modelling and Simulation Of Dji Phantom III Impact Of Human Headmentioning
confidence: 99%
See 2 more Smart Citations
“…This human body model can be seen in Figure 7. The comparison of these novel integrated MBS model simulations has shown that there is a discrepancy between the Hybrid III ATD and a human body model for head and neck injury [16,17]. Neck loads were found to be different fundamentally between the crash dummy and the human model.…”
Section: Mbs Modelling and Simulation Of Dji Phantom III Impact Of Human Headmentioning
confidence: 99%
“…This MBS simulation model allows large variations of UAS impact cases to be evaluated on a validated MBS model of a 50 th percentile human body. The second study [16,17] performed a numerical comparison between the Hybrid III crash dummy and the 50 th percentile human body model. It was found that the human ATD used (i.e.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The human active model (version 3.3), as distributed with MADYMO 2022, was adopted using Matlab and Simulink for running simulations and post-processing. The model was developed and validated primarily to simulate high-severity crashes [22][23][24][25] and extended with postural stabilization for low-severity conditions [26][27][28][29]. It represents a mid-size male adult of 75 kg, 1.76 m standing height and 0.92 m erect sitting height.…”
Section: Human Modelmentioning
confidence: 99%